Students' Perceptions of the Jamaah Tabligh Community Da'wah Model - Harifuddin Harifuddin; Rasyidah Zainuddin; Muhammad Masdar (Palakka : Media and Islamic Communication, 2021)
This study aims to describe student perceptions regarding the model of the Tablighi Jamaat. To achieve this, this study uses a quantitative descriptive method with a survey approach. The population of this study was 500 students of the Faculty of Social and Political Sciences, Bosowa University, and the sample was determined to be 60 using quota sampling technique. The data collection technique used a research instrument with a Likert Scale technique. The data analysis technique used is frequency tabulation with percentage technique. The results showed as follows: (1) The perception of FISIP students at the University of Bosowa towards the Da'wah model of the Tablighi Jamaat group was categorized as 'bad/low'. (2) The effectiveness of the da'wah model was classified as poor/low. The conclusion of this study is that the da'wah model of this group is bad, so it is suggested that this group should change their da'wah model and adapt to the current socio-cultural conditions.